Wild-type minimal inhibitory concentration distributions in bacteria of animal origin in Argentina - Pantozzi, Florencia Laura (2014)
The aim of this study was to determine the antimicrobial resistance profi les of indicator bacteria isolated from domestic animal feces. Minimal inhibitory concentration (MIC) was determined by agar dilution. Interpretative criteria on the basis of wild-type MIC distributions and epidemiological cutoff values (ECOFF or ECV) were used according to the ‘European Committee on Antimicrobial Susceptibility Testing’ (EUCAST) data. Results from 237 isolates of Escherichia coli showed reduced susceptibility for ampicillin, streptomycin and tetracycline, the antimicrobials commonly used in intensive breeding of pigs and hens. Regarding all the species of the genus Enterococcus spp., there are only ECOFF or ECV for vancomycin. Of the 173 Enterococcus spp. isolated, only one showed reduced susceptibility to vancomycin and was classifi ed as ‘non-wild-type’ (NWT) population. This is the fi rst report in Argentina showing data of epidemiological cutoff values in animal bacteria.